The development of Charter of Services in the Education Inspection. Quality factor in citizen attention - Esteban Vázquez Cano; Juan José Arévalo Jiménez; José Luis Gómez de Agüero (ADIDE Federación, 2011)
In this article we analyze the benefits of client service charters in improving the provision of inspection services for education. The development of client service charters in educational administration and, especially in Educational Inspection is a process that projects an image of public service essential for citizen services. Inspection Services are government entities whose functions, powers and liability civil covered in the legislation itself (Spanish Constitution, Organic Law of Education and regional legislation to that effect) require a new way to develop the functions and manage external and internal education inspection services.